Kritik Entitas Homogen Masyarakat Adat pada Putusan MK Nomor 35/PUU-X/2012 Melalui Feminist Political Ecology - Linda Dewi Rahayu (Jurnal Hukum Lex Generalis, 2020)
At the age of independence of the Republic of Indonesia which is approaching the age of a century, the concept of the dream of the welfare state is in fact only limited to rhetoric and does not have a spirit that is in accordance with the mandate of the constitution. The packaging of the law wrapped in the text of the laws and regulations seems to always be less able to create environmental justice and protection of political civil rights and socio-economic rights of the people in every article. Since colonial times there have been various tenure systems implemented by various indigenous communities in Indonesia contrary to the legal framework that supports state control of forest lands and territorialization of forest control, which is the way in which state power over forest areas applies to the boundaries of forest areas that are politically established by the state. Whereas the presence of law should mean that it can bring order and protection to the democratic rights of the people as the object of law. It is always the interests of certain groups that take precedence over the interests of the people. This research is a normative legal research that uses a statutory and conceptual approach, with legal hermeneutic analysis techniques. So that it can be examined by homogeneous entities as a criticism of Constitutional Court Decision No. 35/PUU-X/2012 using the concept of Feminist Political Ecology, so that it can be seen in the reality that indigenous women have not obtained complete recognition as additional rights.